Efficacy and safety of systemic tranexamic acid administration in total knee arthroplasty: A case series. (2020) - Maalouly, Joseph; El Assaad, Donna; Ayoubi, Rami; Tawk, Antonios; Darwish, Mohammad; Aouad, Dany; Lati, Georgio; Darwish, Mohammad; El Rassi, George
Highlights: Tranexamic acid (TXA) can be administered via the intravenous (IV) and/or topical (intra-articular, IA) route, which can possibly interrupt the cascade of events due to hemostatic irregularities close to the source of bleeding. IV TXA was found to be beneficial in terms of blood loss, blood transfusions, and postoperative hemoglobin drop without increasing thromboembolic complications. Our recommendation that 1 g of TXA in IV be given 30 min prior to incision. Abstract: Introduction: Total knee arthroplasty (TKA) are associated with significant postoperative blood loss. Tranexamic acid (TXA) is a potent agent with antiﬁbrinolytic activity, that can be administered via the intravenous (IV) and/or topical (intra-articular, IA) route, which can possibly interrupt the cascade of events due to hemostatic irregularities close to the source of bleeding. However, the literature contains scarce scientiﬁc evidence related to IV only TXA usage in TKA. The current study aims to compare the outcome between patients who were administered IV TXA and a control group in terms of blood loss, transfusion rate, and incidence of deep vein thrombosis (DVT) and thromboembolism (TE). Methods: 110 patients, who underwent TKA were placed into two groups: 1) 34 patients who received IV TXA; and 2) 76 patients in the control group. In the TXA group, patients received an IV TXA dose of 1 g, 30 min before incision. Two drains were placed. Results: Usage of IV TXA showed better results when compared to the control group in terms of mean blood transfusion (0.5 less transfusion during hospital stay), hemoglobin drop (10%). No cases of DVT or TE were noted among the two study groups. Conclusion: Use of IV TXA provided signiﬁcantly better results compared to no TXA use with respect to all variables related to postoperative blood loss in TKA. Moreover, TXA use is safe in terms of incidence of symptomatic DVT and TE.